Ectomycorrhizal fungi and soil enzymes exhibit contrasting patterns along elevation gradients in southern Patagonia (2019)
The biological and functional diversity of ectomycorrhizal (ECM) associations remain largely unknown in South America. In Patagonia, the ECM tree Nothofagus pumilio forms monospecific forests along mountain slopes without confounding effects of vegetation on plant–fungi interactions. To determine how fungal diversity and function are linked to elevation, we characterized fungal communities, edaphic variables, and eight extracellular enzyme activities along six elevation transects in Tierra del Fuego (Argentina and Chile). We also tested whether pairing ITS1 rDNA Illumina sequences generated taxonomic biases related to sequence length. Fungal community shifts across elevations were mediated primarily by soil pH with the most species-rich fungal families occurring mostly within a narrow pH range. By contrast, enzyme activities were minimally influenced by elevation but correlated with soil factors, especially total soil carbon. The activity of leucine aminopeptidase was positively correlated with ECM fungal richness and abundance, and acid phosphatase was correlated with nonECM fungal abundance. Several fungal lineages were undetected when using exclusively paired or unpaired forward ITS1 sequences, and these taxonomic biases need reconsideration for future studies. Our results suggest that soil fungi in N. pumilio forests are functionally similar across elevations and that these diverse communities help to maintain nutrient mobilization across the elevation gradient. © 2019 The Authors. New Phytologist © 2019 New Phytologist Trust